2014
DOI: 10.4161/15592294.2014.967589
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of DNA methylation specific droplet digital PCR (ddPCR) and real time qPCR with flow cytometry in characterizing human T cells in peripheral blood

Abstract: Quantitating the copy number of demethylated CpG promoter sites of the CD3Z gene can be used to estimate the numbers and proportions of T cells in human blood and tissue. Quantitative methylation specific PCR (qPCR) is useful for studying T cells but requires extensive calibration and is imprecise at low copy numbers. Here we compared the performance of a new digital PCR platform (droplet digital PCR or ddPCR) to qPCR using bisulfite converted DNA from 157 blood specimens obtained from ambulatory care controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
(43 reference statements)
1
22
0
1
Order By: Relevance
“…Interestingly, this naïve three CpG score performed relatively well given how little epigenetic information was included (training accuracy 82% versus 96% from the LASSO). For studies without Illumina®450K or Illumina®EPIC data, this score could be implemented by assessing methylation at these three loci using pyrosequencing or other methods (Roessler and Lehmann 2015; Wani and Aldape 2016; Wiencke et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this naïve three CpG score performed relatively well given how little epigenetic information was included (training accuracy 82% versus 96% from the LASSO). For studies without Illumina®450K or Illumina®EPIC data, this score could be implemented by assessing methylation at these three loci using pyrosequencing or other methods (Roessler and Lehmann 2015; Wani and Aldape 2016; Wiencke et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…We developed a single gene qPCR assay of demethylation within the BHLHE40 transcription factor using the highly sensitive droplet digital PCR (ddPCR) technique 23 and consider its potential as a biomarker of NK activation within peripheral whole blood.…”
Section: Foxp3mentioning
confidence: 99%
“…Previous studies have shown that quantitative PCR (qPCR) and ddPCR are both capable of distinguishing clinically significant differences in T-cell proportions and perform similarly to FACS [27]. However, ddPCR technology results in a high-throughput digital PCR with several advantages over qPCR [28, 29].…”
Section: Discussionmentioning
confidence: 99%